Relationship between low IDH and cases of rotavirus diarrhea in Brazil (Research, Society and Development, 2025)
Introduction: Rotavirus is one of the main causes of acute diarrheal diseases (AD), with a major impact on infant mortality. As it is transmitted via the fecal-oral route, it facilitates its spread, especially when low socioeconomic levels are involved. Despite being a self-limiting disease, patients can progress to severe forms and have an unfavorable outcome, raising the alarm for greater epidemiological surveillance. Objective: To assess the relationship between socioeconomic status through the HDI and the incidence of confirmed rotavirus cases. Methods: This is an observational, ecological, analytical study carried out using statistical analysis of the Federative Units (FUs) of Brazil between 2018 and 2022. Results: Observing the relationship between rotavirus incidence and HDI, the statistical correlation is practically null, indicating no association between human development and the incidence of the disease. This result suggests that the MHDI of Brazilian states is not a determining factor in the distribution of the incidence of confirmed rotavirus cases with diarrhea. Discussion: This study shows that the low level of notification of rotavirus can lead to difficulties in obtaining reliable data on the prevalence of this disease. In addition, the way the virus is transmitted and the emergence of new strains reinforce the importance of further studies on this subject. Conclusion: Cases of rotavirus have become more clinically and epidemiologically relevant, reinforcing the importance of control and screening for the earliest possible diagnosis and treatment, avoiding possible complications. It is also necessary to reinforce notification measures so that more studies can be carried out.